THE IMPORTANCE OF SOCIAL AND EMOTIONAL SKILLS - Dominguez, Tiara N. (Acta Scientiae et Intellectus, 2024)
This paper investigates the need for social and emotional skills to become embedded within the daily curriculum. It examines programs that are currently being used globally, and their effectiveness in addressing social and emotional deficits within school age children. Results of the evaluated studies promote the implementation of social and emotional skills. The success found with the integration of SEL skills within the daily curriculum, promotes the preparation of children for postsecondary education, careers, and productive citizenship. The findings of the evaluated programs lead into a discussion revolving around the creation of social and emotional standards, training of teachers on social and emotional standards, and buy-in from all stakeholders, as the necessity for successful implementation of social and emotional skills.